Działalność misji specjalnej OBWE na Ukrainie – sukces, porażka czy impuls do reform? - Natanek, Mirosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
In what follows I analyze, on a macro-level, the role played by the OSCE in negotiating the ceasefire agreement during the conflict in eastern Ukraine. The activity set up to implement the cease-fire arrangements of the OSCE Special Monitoring Mission in Ukraine will be examined in more detail. By analyzing the documents of the OCSE, I will focus on the specific scale, mechanisms, and ways of implementing tasks that result from the Minsk Agreements and which the OSCE Permanent Council imposed on the Mission. This analysis will also be an attempt to assess its efforts so far and to indicate the most important difficulties and obstacles faced by the international community in the process of normalization of the Donbas situation.
Conflict in Donbas. Some remarks concerning the activities of the OSCE Special Minitoring Mission to Ukraine
Keywords: OSCE; Special Monitoring Mission; Donbas; Ukraine